The Relationship between Knowledge and Community Stigma Against ODGJ Patients in the Long Mesengat Community Health Center Working Area - Muiswanah; Gajali Rahman; Badar (Formosa Journal of Science and Technology, 2023)
According to Law No. 18, mental health is a condition where an individual can develop physically, mentally, spiritually and socially so that the individual is aware of his own abilities, can overcome pressure, can work productively and is able to contribute to his community. The stigma against people with mental disorders in Indonesia is very strong. People who experience mental disorders are isolated, and their mental disorders can worsen. In general, people with severe mental disorders (schizophrenia) are treated and given treatment in hospitals. After improving and being sent home, there is no special ongoing treatment for the sufferer. This research uses a purposive sample technique with a cross-sectional research design. The sample size in this study was 88 people. The results of statistical tests using the chi-square test showed a p-value = 0.000 Knowledge of Community Stigma.